2018
DOI: 10.1038/s41598-018-33971-1
|View full text |Cite
|
Sign up to set email alerts
|

Cheetahs discriminate familiar and unfamiliar human voices

Abstract: Domestic species can make the distinction between several human sub-groups, especially between familiar and unfamiliar persons. The Domestication hypothesis assumes that such advanced cognitive skills were driven by domestication itself. However, such capacities have been shown in wild species as well, highlighting the potential role of early experience and proximity with humans. Nevertheless, few studies have been focusing on the use of acoustic cues in wild species and more comparative studies are necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(49 reference statements)
2
12
0
Order By: Relevance
“…identifying and distinguishing strangers' voices) [110]. Captive cheetah, Acinonyx jubatus, also differentiates between familiar and unfamiliar human voices, responding more frequently, for longer, and more quickly to familiar voices than unfamiliar ones [112]. Heterospecific recognition may occur in the wild as well.…”
Section: (D) Social Contexts and Individual Vocal Recognitionmultiplementioning
confidence: 99%
“…identifying and distinguishing strangers' voices) [110]. Captive cheetah, Acinonyx jubatus, also differentiates between familiar and unfamiliar human voices, responding more frequently, for longer, and more quickly to familiar voices than unfamiliar ones [112]. Heterospecific recognition may occur in the wild as well.…”
Section: (D) Social Contexts and Individual Vocal Recognitionmultiplementioning
confidence: 99%
“…Moreover, a growing body of literature has demonstrated that domestic species recognize human faces (dogs: [5]; sheep: [22,23]; horses: [24]) and voices (cats: [3]; horses: [20,21]; pig: [19,25]; and dogs: [26]). Animals not only identify conspecifics and humans through separate sensory modalities (e.g., cats: [3]; dogs: [5]; goats: [27]; sheep: [22,23]; cattle: [6]; and cheetahs: [28]) but they are also capable of integrating identity cues from multiple sensory modalities to recognize them (dogs: [26,29]; horses: [30,31]; goats: [32]; rhesus monkeys: [2,33]; crows: [34], and cats: [35]). This high-level cognitive ability demonstrates that animals form a multimodal internal representation of individuals that is independent of the sensory modality [36].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic, but also captive wild animals, have been shown to present a sensitivity to human attentional states, especially through gaze direction (e.g., dogs: Call et al, 2003;Schwab and Huber, 2006;horses: Sankey et al, 2011;capuchin monkeys: Hattori et al, 2007;red-capped mangabeys: Maille et al, 2012). These abilities may reflect, in the first case, effects of domestication, i.e., selection of animals more skilled in decoding human cues, but also, in both domestic and wild captive animals, shared experiences during repeated interactions (e.g., Leroux et al, 2018). Humans also are very sensitive to their pet's visual attention, as shown recently: dog owners exhibit an increase of oxytocin as a result of their dogs showing long gazes toward them (Nagasawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%